Historical periods of the Islam development in China (Journal of Philosophy Culture and Political Science, 2018)
Authors analyze penetrating of Islam in China and the historical periods of development in China. The features of the development of Islam during the reign of the Tang (618-907 AD), Sung (960-1279 AD), Yuan (1206-1368 AD), Ming (1368-1644 AD) and Qing (1616-1911) dynasties, as well as the influence of Islam on ethno-religious, political, economic and cultural relations of the Chinese society was examined. The study of the Islam history in China is relevant for the solution of modern national, religious, socio-economic and political problems of contemporary Chinese society, and to develop a strategy for the further sustainable development of the Chinese state.Key words: Islam, Confucianism, Buddhism, Daoism, dynasty, national minorities, religion, tradition, Mosque.